Advances in the detection of extrapulmonary tuberculosis: A comprehensive narrative review - Prashant Howal; Saloni Sahu; Mohammad Arfat Ganiyani (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2023)
Tuberculosis (TB) is a highly infectious disease with high prevalence in the economically poor countries in the world with pulmonary and extrapulmonary manifestations. Though major involvement is pulmonary but extrapulmonary tuberculosis burden is quite high & requires a very strong index of suspicion with exhaustive workup for diagnosis. Due to delayed diagnosis and treatment, Extrapulmonary Tuberculosis (EPTB) seems to be more dangerous than Pulmonary Tuberculosis (PTB). EPTB can manifest itself in almost all parts of the body, producing a wide range of symptoms, making its detection tough. Early detection and timely treatment are necessary to prevent the worsening of the symptoms. Newer diagnostic tests like CBNAAT, RT-PCR, and gene sequencing have been introduced over recent years to improve the quality of assessment of this disease. While traditional diagnostic tests like culture, microscopy, and tuberculin tests take days to months to yield results, CBNAAT gives results in only 2 hours, thus making the prognosis better. However, their access is still limited to majorly developed and developing countries, being costlier than the traditional methods. This review focuses on various diagnostic procedures available for the diagnosis of EPTB.